Our house [large type] - Candlish, Louise (Thorndike Press, a part of Gale, a Cengage Company, 2018)
When Fiona Lawson comes home to find strangers moving into her house, she's sure there's been a mistake. She and her estranged husband, Bram, have bird's nest custody, where each parent spends a few nights a week with their two sons at the family home to maintain stability for their children. Now Bram has disappeared... and so have the children. Just how many lies has Bram been weaving? But he's not the only one with things to hide-- and some secrets are best kept to oneself, safe as houses.